Pengembangan Kamus Mini untuk Membantu Pembelajaran Bahasa Arab Kelas VIII di SMP Datok Sulaiman Palopo - Mawardi Mawardi; Mustafa Mustafa; Musdalifa Musdalifa (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to determine the development process, level of validity and level of practicality of small Arabic dictionary media which can be used to support the Arabic language learning process, especially in vocabulary learning. The development of this small Arabic dictionary media is adapted to the learning curriculum and teaching materials for class VIII Junior High Schools. This type of research is research and development (R&D) by adapting the 4D development model which consists of four stages, namely definition, design, development and dissemination. The subjects used in this research were 18 class VIII students at Datok Sulaiman Junior High School. Data collection techniques include observation, interviews, validation sheets, practicality test sheets and student response questionnaires. The result of this development research is a small Arabic dictionary for class VIII students. The product validation test results show that: 1) the material expert validation assessment obtained a score of 96.36%; 2) media expert validation assessment obtained a score of 86.66%; 3) and the practicality test carried out by learning experts obtained a score of 80%. Based on the results of product trials by three experts, it shows that the small Arabic dictionary learning media is very valid and practical to be applied in Arabic language learning.